PENGARUH KEPUASAN KERJA DALAM MEMEDIASI MANAJEMEN PENGETAHUAN, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN KEUANGAN DAN ASET DAERAH KABUPATEN KONAWE SELATAN - Sri Mulyani P.; Ansir Ansir; Nursaban Rommy Suleman (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2023)
The purpose of this study was to examine and analyze the effect of: 1) knowledge management on employee job satisfaction. 2) work environment on employee job satisfaction. 3) knowledge management on employee performance. 4) work environment on employee performance. 5) job satisfaction on employee performance. 6) knowledge management has an effect on employee performance through job satisfaction as a mediation. 7) work environment on employee performance through job satisfaction as a mediation. The research method is using quantitative research. The data used are secondary and primary data. Data analysis usingSmart PLS 3.0 software. Sampling technique using The saturated sample is 51 employees at the Regional Finance and Assets Agency of South Konawe Regency. The results showed that; 1)Management knowledge has a positive and significant effect on job satisfaction. 2) The work environment has a positive and significant effect on job satisfaction. 3) Management knowledge has no significant effect on employee performance. 4) The work environment has a positive and significant effect on employee performance. 5) Job satisfaction has a positive and significant effect on employee performance. 6)The effect of management knowledge on employee performance mediated by job satisfaction has a significant or fully mediated effect. 7). The influence of the work environment on employee performance mediated by job satisfaction has a significant or partially mediated effect.